Assessing the burden of patients with psoriasis through the concept of cumulative life course impairment: A narrative literature review - Anne Crochard; Alexandre Gherardi; Mélanie Hueber Kollen; Seham Issa; Axel Villani (Wiley, 2023)
Abstract Psoriasis can affect diverse facets of patients' lives over time and may lead to irreversible cumulative life course impairment (CLCI). The CLCI concept initially described in 2010 in the context of psoriasis encompasses the intricate interaction between physical, psychological, social and economic burden and is influenced by several factors such as coping mechanisms, personality and external factors. CLCI assessment is conducted to characterise and ultimately mitigate or prevent the patient's burden over the life course. This review aims to give a comprehensive overview of the development and use of the CLCI concept in psoriasis since its inception. A narrative literature review was conducted from 2010 to 2022 and included 19 publications. As original studies on CLCI are scarce, this review primarily relied on case studies and those without longitudinal assessment. The core components of CLCI burden identified in patients' narratives include physical impairment, psychological impairment, stigma, socioeconomic burden and modulating factors. Modulating factors are crucial to mitigate the burden but are not equally explored. The burden associated with psoriasis stands across all dimensions covered by CLCI, thus confirming its suitability in clinical management and future studies. A better understanding of CLCI can support physicians and researchers in improving patients' lives and raising awareness on the necessity to develop early, efficient and patient‐centric interventions. The practical and systematic adoption of CLCI yet relies on the development and psychometric validation of a questionnaire that measures it.